A review of the psychological and familial perspectives of childhood obesity - Latzer, Yael (BioMed Central, 2013)
Childhood obesity is on the rise in both industrialized and developing countries. The investigation of the psychosocial aspects of childhood obesity has been the focus of long- standing theoretical and empirical endeavor. Overweight in children and adolescents is associated with a host of psychological and social problems such as reduced school and social performance, less favorable quality of life, societal victimization and peer teasing, lower self-and body-esteem, and neuropsychological dysfunctioning. Whereas community samples of obese youngsters usually do not show elevated psychopathology, clinically-referred overweight children show elevated depression, anxiety, behavior problems, attention deficit hyperactivity disorder and disordered eating. Parents’ perceptions of their child’s overweight highly influence the well-being of obese children and the way in which they perceive themselves. The present review paper aims to broaden the scope of knowledge of clinicians about several important psychosocial and familial dimensions of childhood obesity: the psychosocial functioning, self and body esteem and psychopathology of overweight youngsters, the influence of children’s perceptions of overweight, including those of the obese children themselves on their well being, and the influence of parental attitudes about weight and eating on the psychological condition of the obese child.